Alice through the looking-glass - Carroll, Lewis (London : Usborne Publishing Ltd, 2009)
Join Alice as she journeys into the topsy-turvy world behind the looking glass. The sequel to Alice's Adventure in Wonderland has an equally bizarre plot and even more unforgettable characters.
Shelving Location Readers Section. Fiction Book Section
Keywords: Children's Fiction Stories